English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

I changed it to y^9 x^4/ x^6 y^2 but what do I do from there? I don't need to solve anything, just simplify it with positive exponents in the final answer.

Thanks for your help!!

2007-12-12 04:33:18 · 3 answers · asked by ♫ ∫aoli 4 in Science & Mathematics Mathematics

3 answers

(x^-2)^3= x^-6
so, (x^-2y^3)^3= y^3x^-6
(x^-2y)^-2 = x^-4 y^-2
You have y^3 x^-6 x^-4 y^-2 = y^1 x^-10
=y/x^10

2007-12-12 04:42:08 · answer #1 · answered by cidyah 7 · 0 2

(x^-2 y^3)^3 (x^-2 y)^-2
=(y^3/x^2)^3 *( y/x^2)^-2
= (y^9/x^6) * 1/y^2/x^4
= y^7/ x^2

2007-12-12 04:42:18 · answer #2 · answered by ironduke8159 7 · 1 0

The next steps are to simplify everything...

i.e. x^-6y^3 / x^2y^5 can be rewritten as,
x^(-6-2)y^(3-5)
x^-8y^-2
In this case the final answer can be left as,
1/ (x^8y^2)

Hope you figure out the solution for your question. Good luck!

2007-12-12 04:48:45 · answer #3 · answered by Silver 3 · 0 0

fedest.com, questions and answers